"Ethnographic" thematic phenomenography: A methodological adaptation for the study of information literacy in an ontologically complex workplace. Issue 2 (6th March 2019) - Forster, Marc
Abstract : Purpose: The workplace is a context of increasing interest in information literacy research, if not necessarily the most visible (Cheuk, 2017 ). Several studies have described contextual, relationship-based experiences of this subjective, knowledge-development focussed phenomenon (Forster, 2017b ). What research contexts and methods are likely to be most effective, especially in workplaces which contain professions of widely differing ontologies and epistemological realities? The paper aims to discuss these issues. Design/methodology/approach: An analysis and description of the value and validity of a "qualitative mixed methods" approach in which the thematic form of phenomenography is contextualised ethnographically. Findings: This paper describes a new research design for investigation into information literacy in the workplace, and discusses key issues around sampling, data collection and analysis, suggesting solutions to predictable problems. Such an approach would be centred on thematic phenomenographic data from semi-structured interviews, contextualised by additional ethnographic methods of data collection. The latter's findings are analysed in light of the interview data to contextualise that data and facilitate a workplace-wide analysis of information literacy and the information culture it creates. Originality/value: Insights from recent research studies into information literacy in the workplace have suggested the possibility of an epistemologically justifiable, qualitative mixed methods design involving an ethnographic contextualisation of a thematic phenomenographic analysis of the information culture of an ontologically varied and complex workplace – with the potential for descriptive contextualisation, categorisation and generalisability.